Training Procedures for Making Fruit Yoghurt to Housewives to Help Increase Husband's Income in Bandar Khalipah Village - Irda Wahidah Nasution; Nurul Hidayah Nasution (Edumedia Solution, 2022)
Yoghurt is one of the health drinks that tastes fresh and sour and is liked by many people, adults and children. Yoghurt made by fermentation using Lactobacillus bulgaricus and Streptococcus thermophilus bacteria inoculated in milk will produce a semi-solid consistency of milk and a slightly sweet-sour taste and can eliminate the sharp odor of goat's milk. The PkM implementation stage is like a training activity, namely this activity there are also several events which are held for 3 days, namely on 24-26 July 2019. The target audience is housewives and community leaders in Bandar Khalipah Village, which includes 50 people consisting of various housewives located at Jalan Angsana No. 3 Market XI Tembung. This PkM method will be carried out through training on the benefits of yogurt for health through media presentations, demos followed by questions and answers. The training materials include: introduction, yogurt bacterial culture, benefits of yogurt and methods of making yogurt. While the way of making yogurt is done by practicing together between the demonstrators and the audience. The method of making yogurt consists of preparation, pasteurization, bacterial preparation, mixing bacteria with milk, storage and storage. The participants of this activity program were very enthusiastic about listening to materials and practices on how to make yogurt so that they could practice it themselves at home. In addition, they also see business opportunities to improve family welfare both financially and healthily. With a positive response from partners, finally this community service can be useful for housewives so that it can improve family welfare.